Effects of intravenous clonidine on hemodynamics and plasma cortisol level during laparoscopic urological surgeries in a tertiary care hospital - Saha, Ananya; Mukherjee, Maitreyee; Sikdar, Sovan; Chatterjee, Sajib; Laha, Arpita (Asian Journal of Medical Sciences, 2022)
Background: Laparoscopic urologic surgeries causes rise in Blood pressure and heart rate. Maintenance of hemodynamics is an essential part of anaesthetic management. Aims and Objectives: The aim of the study was to observe the effects of intravenous clonidine on heart rate (HR) and mean arterial pressure (MAP) and plasma cortisol level during laparoscopic surgeries. Materials and Methods: In this ethical committee approved double-blind prospective interventional study, 50 adult patients of both sexes with ASA I and II were randomly allocated to two groups: Group C (3 mcg/kg Clonidine in 20 ml of Normal saline) and Group P (20 ml Normal saline). HR and MAP were recorded at different time intervals and blood samples were drawn before induction and after reversal from general anesthesia. Results: In Group P there was a significant increase in variables during intubation, pneumoperitoneum and release of gas from the abdomen (P<0.001). In Group C mean plasma cortisol level increased from 19.36±1.49 (before induction) to 28.60±1.21 (after reversal) and in Group P from 19.33±1.30 to 32.28±1.66. Conclusion: Clonidine may be a suitable and safe medication to attenuate hemodynamic stress response during laparoscopic surgeries.